2020
DOI: 10.3390/ijms21041177
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage and DNA Damage Response in Chronic Myeloid Leukemia

Abstract: DNA damage and alterations in the DNA damage response (DDR) are critical sources of genetic instability that might be involved in BCR-ABL1 kinase-mediated blastic transformation of chronic myeloid leukemia (CML). Here, increased DNA damage is detected by γH2AX foci analysis in peripheral blood mononuclear cells (PBMCs) of de novo untreated chronic phase (CP)-CML patients (n = 5; 2.5 γH2AX foci per PBMC ± 0.5) and blast phase (BP)-CML patients (n = 3; 4.4 γH2AX foci per PBMC ± 0.7) as well as CP-CML patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…The Chk2 kinase was activated in all samples, and the phosphorylation-specific band appeared to be strong in most patients (Figure 1b). These data are consistent with recently published evidence for ongoing DNA damage and DDR detected by activated ATM, Chk2, and γH2AX accumulation in PB-MNCs of de novo untreated CP-CML patients [39]. In contrast to strong Chk2 activation in CML cells, lysates prepared from cells obtained from PV patients in their proliferative phase showed only modest evidence of activated Chk2 (i.e., displayed lower signal of phosphorylated Chk2 compared to CML cells), whereas the unphosphorylated form of Chk2 was barely detectable in these samples (Figure 1b).…”
supporting
confidence: 93%
See 1 more Smart Citation
“…The Chk2 kinase was activated in all samples, and the phosphorylation-specific band appeared to be strong in most patients (Figure 1b). These data are consistent with recently published evidence for ongoing DNA damage and DDR detected by activated ATM, Chk2, and γH2AX accumulation in PB-MNCs of de novo untreated CP-CML patients [39]. In contrast to strong Chk2 activation in CML cells, lysates prepared from cells obtained from PV patients in their proliferative phase showed only modest evidence of activated Chk2 (i.e., displayed lower signal of phosphorylated Chk2 compared to CML cells), whereas the unphosphorylated form of Chk2 was barely detectable in these samples (Figure 1b).…”
supporting
confidence: 93%
“…Therefore, a better understanding of BCR-ABL and JAK2 V617F roles in the DNA damage response and disease pathophysiology can help to identify potential dependencies exploitable for therapeutic interventions.CML is characterized by an indolent, chronic phase (CP) preceding an acute transformation to BC. Failure of DNA damage repair and loss or malfunction of DDR components accompanied by accumulation of DNA damage and genomic instability has been considered in CML evolution [38,39]. It was proposed that BCR-ABL-expressing cells feature reduced activation of the ATR-Chk1-mediated DDR signaling, with ensuing accumulation of substantial genomic instability due to replication stress and oxidative damage.…”
mentioning
confidence: 99%
“…To investigate whether the accumulation of ROS-induced DNA damage and defective DNA damage response (DDR) rates are associated with chronic myeloid leukemia (CML), a myeloproliferative neoplasm, the study by Popp et al [ 10 ] examined the levels of double strand breaks (DSBs) and DDR in CML patients by immunofluorescence microscopy and Western blotting. High DSB production, detected by the γH2AX foci analysis, was found in chronic, accelerated and blast phases of CML patients as well as in those with loss of major molecular response in respect to controls or CML patients with deep molecular response.…”
mentioning
confidence: 99%
“… 56 The incidence of ACAs among CP-CML patients is 5%, while 60%-80% ACAs are detected in BP-CML. 2 , 57 , 58 Previously, the European Leukemia Network (ELN) recommended that ACAs present at the time of a new diagnosis be defined as a warning signal and that newly emerging ACAs for treatment be defined as a failure. However, it was later found that the ACA subtype could be used to predict the patient outcome.…”
Section: Evidence That Drives CML Progression Is Increasingly Explored At Different Molecular Levelsmentioning
confidence: 99%
“…The disease is caused by the BCR-ABL fusion gene generated from the t (9;22)(q34;q11) reciprocal translocation, encoding the BCR-ABL oncoprotein, which constitutively activates ABL kinase and drives hematopoietic cell proliferation and leukemic transformation. [1][2][3][4][5][6] CML is a natural triphasic course disease starting with the indolent CP, which is characterized by a remarkable increase in myeloid precursors and mature cells and lasts approximately 3-5 years. 7 Without therapeutic intervention, after a median interval of 3-18 months, the disease spontaneously progresses to AP and eventually to highly aggressive BP, characterized by a rapid expansion of primitive cells in the bone marrow that spill into circulation, 8,9 similar to acute leukemia.…”
Section: Introductionmentioning
confidence: 99%